PENINGKATAN PERAN IBU DALAM PENCEGAHAN STUNTING PADA BALITA DI KABUPATEN BULUKUMBA: PENINGKATAN PERAN IBU DALAM PENCEGAHAN STUNTING PADA BALITA DI KABUPATEN BULUKUMBA - Jusni; Akhfar, Kurniati; Isnaeny, Isnaeny; Rahmawati, Rahmawati (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
The percentage of stunted toddlers in Indonesia is still high and is a problem that must be addressed. The government has made various efforts to prevent and overcome the problem of stunting in toddlers through various programs. However, the results have not been able to overcome the problem of stunting. The mother's role is a key factor in preventing stunting. The aim of this activity is to increase mothers' knowledge about their role in preventing stunting. This activity was carried out on December 21 2023. Before the education was carried out, a pre-test was carried out to determine knowledge of the mother's role in preventing stunting in children and a post-test was carried out after the stunting prevention education. The results of the service showed changes in mothers' knowledge after providing education on the role of mothers in preventing stunting through zoom meetings to commemorate Mother's Day